Hypoxia Regulates the Proliferation and Apoptosis of Coronary Artery Smooth Muscle Cells Through HIF-1α Mediated Autophagy in Yak - Shanshan Yang; Yan Cui; Rui Ma; Sijiu Yu; Hui Zhang; Pengfei Zhao; Junfeng He (Biomolecules)
Cell proliferation and migration mediated by hypoxia-inducible factor-1α (HIF-1α) are important processes of hypoxic cardiac vascular remodeling. HIF-1α also regulates the physiological hypoxic adaptation of the coronary artery in the yak heart, but the potential mechanism remains to be completely elucidated. In this study, coronary artery proliferation increased with age and hypoxia adaptation time. In vitro analysis showed that hypoxia can promote the proliferation of coronary vascular smooth muscle cells (CASMCs). Meanwhile, HIF-1α plays an important role in the regulation of proliferation and migration under hypoxia. Autophagy regulates cell proliferation and migration to participate in hypoxia adaptation in plateau animals. Here, the level of autophagy increased significantly in yak coronary arteries with age and was regulated by HIF-1α-mediated hypoxia. In addition, autophagy could also mediate the hypoxic effect on the proliferation and migration of CASMCs. In summary, the results revealed that the increase in yak heart coronary artery thickening with age increases vascular smooth muscle cell proliferation and migration, mainly achieved through hypoxia-mediated HIF-1α-regulated autophagy. These results contribute to understanding how the heart adapts to life in a hypoxic environment.